Responsible tourism: an inductive approach - Ramachandran, Sridar (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
The purpose of this study is to determine responsible tourism indicators. An inductive approach is used to achieve this objective. This paper adapts the 4-phase research process of design principle, data elicitation, data analysis and knowledge interest. The empirical assessment is undertaken at Taman Negara (National Park), Malaysia. In-depth interviews were carried out to capture the indicators for responsible tourism from a stakeholder’s perspective. Four broad categories out of the 68 stakeholders who participated in this survey include local community, domestic tourists, international tourists and policy makers. Political, ecological, social, economic, technological and cultural are the six dimensions used as a topic guide during the in-depth interviews. The findings of this paper discuss the underlying meaning of responsible tourism indicators from various stakeholders’ perspective.